2016
DOI: 10.1371/journal.pone.0160111
|View full text |Cite
|
Sign up to set email alerts
|

Classification of High Intensity Zones of the Lumbar Spine and Their Association with Other Spinal MRI Phenotypes: The Wakayama Spine Study

Abstract: IntroductionHigh intensity zones (HIZ) of the lumbar spine are a phenotype of the intervertebral disc noted on MRI whose clinical relevance has been debated. Traditionally, T2-weighted (T2W) magnetic resonance imaging (MRI) has been utilized to identify HIZ of lumbar discs. However, controversy exists with regards to HIZ morphology, topography, and association with other MRI spinal phenotypes. Moreover, classification of HIZ has not been thoroughly defined in the past and the use of additional imaging paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 48 publications
4
43
0
Order By: Relevance
“…This bright area surrounded by a low-intensity (black) signal of the AF is appreciably brighter than the CSF signal at the same level on sagittal T2W MRI of L1 to S1. (17,62,63) HIZ has been shown to correlate with annulus damage and increased pain; it is also consistent with findings on discography. (64,65)…”
Section: Noninvasive Diagnostic Tools For Discogenic Painsupporting
confidence: 84%
See 1 more Smart Citation
“…This bright area surrounded by a low-intensity (black) signal of the AF is appreciably brighter than the CSF signal at the same level on sagittal T2W MRI of L1 to S1. (17,62,63) HIZ has been shown to correlate with annulus damage and increased pain; it is also consistent with findings on discography. (64,65)…”
Section: Noninvasive Diagnostic Tools For Discogenic Painsupporting
confidence: 84%
“…It commonly requires prolonged treatment, has mixed‐to‐poor surgical outcomes, and opioids are often prescribed . Many studies have demonstrated high sensitivity of pain to IVD pathologies on MRI including high‐intensity zones and Modic changes, although this sensitivity is often not specific to pain presentation. The absence of IVD degeneration on MRI is associated with significantly reduced pain, making it a more specific measure .…”
Section: Introductionmentioning
confidence: 99%
“…Three comparative studies indicated the significant association between HIZs and LBP [ 12 17 ] (Table 3 ). Wang et al [ 14 ] reported a clinical series, which included 623 patients (337 males and 286 females, age 50.1 ± 15.4 years), and 200 patients (32.1%) exhibited HIZs in at least one disc.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no consensus as reports have contradictory evidence and are based on limited evidence from studies without control groups, underpowered, or heterogeneous population studies [ 11 23 ]. Regarding some previous studies using discographic injection for HIZ, the relationship between the presence of lumbar HIZs with a concordant pain response on provocative discography was noted as a significant MRI biomarker of the diagnosis of discogenic LBP [ 11 , 12 ]. On the other hand, Ricketson et al [ 27 ] and Buirski et al [ 34 ] were not able to demonstrate a statistically significant correlation between the presence of HIZs and pain concordant with the usual symptoms elicited during provocative discography [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation